2016
DOI: 10.3171/2016.8.focus16277
|View full text |Cite
|
Sign up to set email alerts
|

Late pediatric ventriculoperitoneal shunt failures: a Singapore tertiary institution's experience

Abstract: OBJECTIVE The introduction of ventriculoperitoneal shunts changed the way hydrocephalus was treated. Whereas much is known about the causes of shunt failure in the first few years, there is a paucity of data in the literature regarding the cause of late shunt failures. The authors conducted a study to find out the different causes of late shunt failures in their institution. METHODS A 10-year retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Shunt fractures result from calcification, fibrosis, and tethering within tissues, which predispose the catheter to rupture when biomechanical tension is applied [ 3 ]. A follow-up study showed that aged implants become fragile within an average of 5 years after the appearance of calcification in pediatric patients [ 4 ]. Tubing fractures occur most often in children when their height increases rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Shunt fractures result from calcification, fibrosis, and tethering within tissues, which predispose the catheter to rupture when biomechanical tension is applied [ 3 ]. A follow-up study showed that aged implants become fragile within an average of 5 years after the appearance of calcification in pediatric patients [ 4 ]. Tubing fractures occur most often in children when their height increases rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…[13] The requirement of shunt revisions varies from 6 months to 20 years after the VPS insertion or last shunt revision. [123] Bowel perforation is also occurring in up to 2% of the cases, and most of the time, the bowel perforation is without peritonitis. Colon is the most common site for hollow viscus perforation by peritoneal catheter, although perforation of the small bowel, stomach, and other hollow viscus has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ventriculoperitoneal shunt (VPS) insertion for the treatment of hydrocephalus is associated with several complications, including infections, mechanical failure, obstruction, bowel perforation with or without extrusion through natural orifices, nonvisceral perforation, shunt migrations, and shunt disconnection. [123] Colon is the most common site for hollow viscus perforation by the peritoneal catheter, but perforation of the small bowel, stomach, and other hollow viscus has also been reported. [1345] Disconnection of VPS catheter is also a well-known complication and is observed more in multicomponent shunt systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ventriculoperitoneal (V-P) shunting is the most widespread used treatment for patients with hydrocephalus. However, some studies have shown that in a pediatric population for shunts, the V-P shunt malfunction rate can be 41–58% [1], including shunt catheter blockage, infection, and over- or under-drainage. The usual clinical presentation of V-P shunt malfunction was headache, vomiting, and dizziness [2].…”
Section: Introductionmentioning
confidence: 99%